Electrochemical study of the electrodeposition and intercalation of sodium into graphite from sodium chloride as the first step of carbon nano-tubes formation - Borisenko N.; Sytchev J.; Kaptay G. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The mechanism of sodium reduction in sodium chloride melt at three different electrodes has been investigated by means of cyclic voltammetry. The definition of so-called ‘thermodynamic’ or ‘material balance’ reversibility has been introduced. It has been shown that the dissolution of sodium in the melt is an important factor in the overall process in the whole range of polarization rates. The adsorption of sodium on glassy carbon and graphite plays an important role in the reduction of sodium at polarization rates below 1 V/s, and it makes the process reversibility higher compared to molybdenum. The intercalation of sodium into the graphite lattice decreases the overall reversibility of the process at low polarization rates.